A Study on Cattle Health and Disease Dynamics in Urban and Peri-Urban Areas of Karachi (Journal of Agriculture and Veterinary Science, 2026)
Cattle rearing constitutes an important part of Karachi`s urban and peri urban economy, providing a large part of the milk and meat production in the city. Nevertheless, infectious and management related diseases often undermine the health and productivity of the cattle in these regions. In this paper, the health conditions and disease dynamics of the cattle populations (n= 3500) in the urban and peri-urban areas of Karachi has been studied considering the major infectious diseases like Lumpy Skin Disease (LSD), Foot and Mouth Disease (FMD), Brucellosis, and Bovine Tuberculosis. The methodologies were field surveys, interviews with farmers, and veterinary records to assess the management practices in farms, biosecurity, and disease prevalence. The results indicate that poor hygiene, housing, animal movement, and less availability of vaccination is some of the major contributors to the transmission and reoccurrence of the diseases. The findings show that there is a significant difference in the prevalence of diseases in the districts. The most common condition of all was Mastitis with the highest rates recorded in District Korangi (17%), then District West (12.4%), and District Malir (10.5%). Anthrax was also predominant with a significant prevalence of 16% and 15.8 % in District Malir and Korangi respectively. District West recorded the highest percentage of Bovine Johne Disease (6.4%), and Black Quarter and Hemorrhagic Septicemia were also relatively high in Korangi (6.9% and 3.7%, respectively). There were significant differences in the prevalence of pneumonia in District Malir (11.57%) against other districts. Conversely, District South and District Central had the lowest prevalence rates of most diseases.The research highlights that animal health management programs, regular disease surveillance and farmer`s education are required as a measure to curb the risks of diseases. Intensifying these measures will lead to improved productivity of cattle, less economic wastage and a more sustainable and robust livestock industry in Karachi.